A broken amalaka - Temples of India Project Team (Jio Institute, 2024)
Broken fragments and debris from the original temple assembled on the north face of the adhisthana. Most fragments assembled here were once part of the shikhara of the original temple, other subsidiary structures, and associated parts like the amalaka (notched disc) as seen here.